Genetic Variability of Maize (Zea mays L.) Genotypes on Some Yield and Yield Components at Haramaya, Eastern Ethiopia - Mekuannet Belay Kebede; Degefa Gebissa (Turkish Journal of Agriculture: Food Science and Technology)
Genetic improvement in components of economic importance along with maintaining a sufficient amount of variability is always the desired objective in the any maize (Zea mays L.) breeding program which will be handled under the conditions of Haramaya, Eastern Ethiopia. Therefore, an experiment was conducted using (27) and (3) check/control varieties to determine the genetic variability of maize genotypes at Haramaya, eastern Ethiopia. The study results revealed that significantly the tallest plant heights for (PH) were recorded from (3) (170 cm) and (18) (167.5 cm) genotypes whereas the shortest PH were recorded from (13) (117.5 cm) and (23) genotypes (120 cm). Good plant aspects (PA) were obtained from genotype 12, 22 and 26 (PA-1.5) and poor PA were attained from genotype 1 (PA-2.5). Besides, genetic and phenotypic variances were estimated for seven components. The highest genotypic coefficients variation (GCV) and phenotypic coefficients of variation (PCV) were calculated from grain yield (GY – 23.39%). Comparatively the higher GY were attained from the genotypes of 3, 9 and 12. It can be concluded that almost all components of the PCV are greater than the GCV. Superior selected genotypes are recommended to the researchers /breeders to develop disease resistant and high yielder varieties to increase maize production by farmers under Haramaya and other similar agroecologies.